Submission to the Queensland Youth Strategy - Monash Centre for Youth Policy and Education Practice (CYPEP); Lucas Walsh; Beatriz Gallo Cordoba; Blake Cutler (Monash University, 2022)
The Monash Centre for Youth Policy and Education Practice submitted a response to the Queensland Youth Strategy consulation in November 2022. Our response drew on what young Queenslanders have told us about the issues that are important to them, including housing, employment, education, climate change, health and wellbeing, equality, and involvement in decisions that affect them.
Keywords: Social policy